An Explorative Assessment of the Importance of Mediterranean Coralligenous Habitat to Local Economy: The Case of Recreational Diving - Chimienti, Giovanni; Stithou, Mavra; Mura, Ilaria Dalle; Mastrototaro, Francesco; D’Onghia, Gianfranco; Tursi, Angelo; Izzi, Carla; Fraschetti, Simonetta (Journal of Environmental Accounting and Management, 2026)
There is an increasing recognition of the importance of cultural ecosystem services of marine habitats for supporting the management of the marine environment. However, these services are still largely unknown compared to other ecosystem services (e.g. provisioning services) owing to the challenge of quantifying and valuing them. Linking human welfare to marine ecosystem services can contribute to the sustainable development of marine areas and use of marine resources. Coralligenous bioconstructions represent a key habitat of the Mediterranean continental shelf because of their structural and functional importance, as well as for their high aesthetic value. In this study, we considered SCUBA diving frequentation in the Apulia region (Mediterranean Sea, Italy) and the generated revenue related to the existence of coralligenous habitat. A market impact of €4.7 M in 2014 was estimated through a survey questionnaire distributed to diving centers across the area (about 1000 km of coastline). Despite the assessment underestimates the impact of coralligenous habitat, it highlights the magnitude of importance of this habitat and the opportunities it provides to local economy. The results emphasise also the potential of including economic analysis to increasing awareness among stakeholders, including the general public and decision makers, in setting priorities for conservation and coastal management decisions.